Application of the Team Quiz Model to the Material of the Human Food Digestion System to Improve Student Learning Outcomes at SMP Negeri 2 Banda Aceh - Nurul Hidayanti; Khairil Khairil; Djufri Djufri; Asiah Asiah; Andi Ulfa Tenri Pada Ulfa Pada (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2020)
The study entitled Application of the Team Quiz Model to the Material of the Human Food Digestion System to Improve Student Learning Outcomes at SMP Negeri 2 Banda Aceh was conducted in November 2016. The purpose of this study was to investigate the application of the Team Quiz to the material of the human food digestion system. at SMP Negeri 2 Banda Aceh. Data collection was carried out twice, namely Pre-test and Post-test. This research approach is quantitative. The design of this experiment uses the Pre-test Post-test Control Group Design. The sample of this study for the control class is students of class VIII-6 and the experimental class is students of class VIII-7. The data in this study were analyzed by t test, with a significance level α = 0.05. The results of the analysis of the average value of Pre-test 42.62 in the control class, 41.48 for the experimental class. While the Post-test mean value of 77.76 in the control class, 87.66 for the experimental class. Based on the above calculation, tcount ttable is 3.68. 1.6 so that h0 is rejected. Keywords: Team Quiz, Improving Learning Outcomes, Food Digestion System Penelitian yang berjudul Penerapan Model Team Quiz  Pada Materi Sistem Pencernaan Makanan Manusia untuk Meningkatkan Hasil Belajar Siswa di SMP Negeri 2 Banda Aceh telah dilaksanakan pada bulan November 2016. Tujuan pada penelitian ini untuk mengetahui penerapan Team Quiz  pada materi sistem pencernaan makanan manusia hasil belajar siswa meningkat di SMP Negeri 2 Banda Aceh. Pengumpulan data dilakukan sebanyak dua kali, yaitu Pre-test  dan Post-test. Pendekatan penelitian ini adalah kuantitatif. Bentuk desain eksperimen ini  menggunakan Pre-test Post-test Control Group Design. Sampel penelitian ini untuk kelas kontrol adalah adalah siswa kelas VIII-6 dan kelas eksperimen adalah siswa kelas VIII-7. Data pada penelitian ini dianalisis dengan uji t, yaitu dengan taraf signifikan α = 0,05. Hasil analisis nilai rata-rata Pre-test 42,62 pada kelas control, 41,48 untuk kelas eksperimen. Sedangkan nilai rata-rata Post-test 77,76 pada kelas kontrol, 87,66 untuk kelas ekperimen. Berdasarkan perhitungan diatas diperoleh thitung ttabel yaitu 3,68 . 1,6 sehingga h0 di tolak.      Kata Kunci : Team Quiz, Meningkatkan Hasil Belajar, Sistem Pencernaan Makanan